Martha Kanter reflects on higher education challenges for students with disabilities. Issue 5 (12th November 2020) - Pena, Maria
Abstract : Martha Kanter, former Undersecretary of Education for the U.S. Department of Education, shared her thoughts on the challenges facing disability services offices and students with disabilities — and how to address them.